Chemical modification and polyaniline functionalization of graphene using in situ generated diazonium salts - ELLIARD ROSWELL, YANZA (Archīum Ateneo, 2012)
Liquid-phase exfoliated graphene sheets in N,N-dimethylformamide (DMF) was subsequently modified by reductive dediazotization of p-substituted phenyldiazonium in situ diazotized from p-aminobenzoic acid, p-nitroaniline and sulfanilic acid using sodium nit